Clarifying the identities of Saccostrea scyphophilla (Péron & Lesueur, 1807) and S. mordax (Gould, 1850) (Bivalvia: Ostreidae) from the Indo-Pacific - Lukehurst, Sherralee S.; Tan, Siong Kiat; Tan, Koh Siang; Dehm, Jasha; Hewavitharane, Chinthaka; Wells, Fred E. (Zootaxa, 2026)
There have been numerous morphological and genetic studies of oyster taxonomy, but species relationships, particularly in the genus Saccostrea, are poorly understood. The present paper uses shell morphology and DNA sequences to demonstrate Saccostrea scyphophilla (Péron & Lesueur) and S. mordax (Gould) are distinct species. A neotype is designated for S. scyphophilla. Synonyms are Saxostrea amasa Iredale, Ostrea mordax var. cornucopiaeformis Saville-Kent and provisionally Ostrea forskali var. sueli Jousseaume, while Saccostrea mordoides Cui et al. is a synonym of S. mordax. The tropical oyster reef formed by S. scyphophilla at Point Quobba, Western Australia, is the first recorded reef constructed by this species. The present paper provides a basis for further work elucidating the species of Saccostrea in the Indo-West Pacific region.